Application of Story Telling Model in Optimizing Children's Speaking Ability - Ainy Rambe, Syarifah; Konadi, Husrin (IAIN Takengon, 2022)
The development of speaking skills is a very important ability to be developed at an early age. This study aims to determine the children's speaking ability through speaking activities using the story telling method in children of group B Raudhatul Athfal Buntul Siri, Kebayakan sub-district, Central Aceh district. The speaking activity uses a varied and interesting story telling method so that it can motivate children's interest. This type of research is a collaborative classroom action research with Kurt Lewin's model. Each cycle consists of four stages: planning, implementation, observation and reflection. The research subjects were children of Raudhatul Athfal Buntul Siri, Kebayakan District, Central Aceh Regency, totaling 21 children. The object of the research is the children's speaking ability through the story telling method. Data collection techniques using observation and documentation. The instrument used in the observation is in the form of an assessment sheet. The data analysis technique used is descriptive analytic with quantitative data. The results of this study indicate an increase in children's speaking skills through the story telling method in Raudhatul Athfal Buntul Siri, Kebayakan District, Central Aceh Regency. This is evidenced by the achievement of indicators of the success of children's speaking ability which has reached 80%. The child's speaking ability has increased after the researcher gave the action which was carried out through several stages and processes, namely: 1). The teacher uses story books during story telling activities 2). Children are asked to repeat the story that has been told in a simple way 3). Children are given the opportunity to speak in front of their classmates 4). Teachers always provide motivation so that children become enthusiastic and enthusiastic in participating in speaking activities